Seychelles Programmatic Public Expenditure Review Policy Notes : Health, Education, and Investment Management - World Bank (Washington, DC, 2014)
Since 2008, the Government of Seychelles has successfully undertaken major reforms to secure macroeconomic stability and create conditions for sustainable, private sector-led growth. The continuous strengthening of Seychelles' public financial management (PFM) system plays a central role in facilitating fiscal consolidation and improving the delivery of government services. Over the past few years, the government has implemented a series of reforms to address public sector governance, including: (i) modernizing the public sector and improving the alignment of institutions with policy and service delivery mandates; (ii) rolling back the government's role in commercial activities by reducing the large number of parastatals, improving management, and introducing a new wage bill together with the private sector; and (iii) redefining the accountability structure between the government agencies responsible for service delivery. Despite the government's ambitious macroeconomic reform program and its efforts to strengthen the PFM system, measures to improve the efficiency of public investment management (PIM) have received only limited consideration. Challenges to the efficient use of public resources hamper the government's ability to meet urgent social needs and improve access to basic services. This note aims to provide an objective assessment of the strengths and weaknesses of Seychelles' PIM system and to recommend measures for improving the quality of capital spending.